Bilingualism and Diglossia in The Novel Api Tauhid - Sulaeman, Islamiyah; Sulaeman, Insyirah (Aksara: Jurnal Bahasa dan Sastra, 2023)
This study aims to analyze the forms and causal factors of bilingualism and diglossia phenomena in the conversations of characters in novel Api Tauhid. The research methodology employed is descriptive analysis, with data collection techniques including reading and recording. Data analysis involved data reduction, presentation, and conclusion drawing. The study identified 9 instances of bilingualism and 13 instances of diglossia in the characters' conversations. Bilingualism was found to be influenced by speakers' proficiency in multiple languages, speaker identity, as well as the location and situation of the conversation. On the other hand, diglossia was influenced by dialect differences, speaker identity, and bilingual abilities. These language phenomena in the novel highlight the integration of bilingual skills in people's lives. The implications of this study suggest that bilingualism and diglossia are prevalent language phenomena in contemporary literature, reflecting the influence of multilingualism in society. These findings emphasize the need for a greater understanding of how language choices and code-switching affect communication dynamics and cultural identity in literary works. However, this study has certain limitations, such as its focus on a specific novel and the subjective interpretation of language phenomena. Future research could expand the scope by including a broader range of literary works and employing more objective measures to analyze bilingualism and diglossia.